2017
DOI: 10.21608/adjalexu.2017.57849
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cortical Lag Screws and Miniplates for Internal Fixation of Mandibular Symphyseal Region Fractures

Abstract: INTRODUCTION: The management of facial trauma is one of the most rewarding and demanding aspects of oral and maxillofacial surgery. Being the most prominent mobile bone of the facial skeleton, mandible fracture occurs more frequently than any other fracture. OBJECTIVES: The aim of this study was to compare the outcomes of treatment by the use of cortical lag screws versus miniplates, in patients who have a fracture in the mandibular symphyseal region. MATERIALS AND METHODS: The present study was conducted on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…showed no occlusal discrepancies at any follow-up periods. [ 3 25 ] Infection or swelling in this study was observed one week postoperatively in one patient each from the 3D plate group and the miniplate group, which was statistically nonsignificant and correlated with studies performed by Jimson et al , Prasad et al , and Jain et al . [ 9 13 26 ]…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…showed no occlusal discrepancies at any follow-up periods. [ 3 25 ] Infection or swelling in this study was observed one week postoperatively in one patient each from the 3D plate group and the miniplate group, which was statistically nonsignificant and correlated with studies performed by Jimson et al , Prasad et al , and Jain et al . [ 9 13 26 ]…”
Section: Discussionsupporting
confidence: 86%
“…Besides supplying compression between the fragments to support healing, fracture stabilization is firm, and tissue exposure is reduced. [ 3 4 ] In 1973, Michelet introduced miniplates via a transoral approach and Champy further refined and researched miniplates. The approach to rigid plate fixation was then modified with progressively smaller plates and less reliance on compression.…”
Section: Introductionmentioning
confidence: 99%
“…However, the three fixation techniques were comparable regarding stability and radiological outcomes. In a recent two reports by Elhussein et al [19] , and El Nakeeb et al [20] , the rates of satisfactory clinical and radiological outcomes were comparable between miniplates and lag screw and 3D plates, respectively. Nonetheless, other published reports showed significantly better improvement in early clinical and radiological outcomes following lag screws, compared to miniplates [21,22] .…”
Section: Discussionmentioning
confidence: 81%
“…Similar findings were reproted by Bhatnagar et al [25] , and Agnihotri et al [26] . According to Elhussein et al [19] , both lag screws and 3D plates are associated with better intra-fracture stability, less manipulation, and less bone drilling; which can result in lower rates of postoperative edema and pain.…”
Section: Discussionmentioning
confidence: 99%